Integrative taxonomy reveals a new species of Characidium (Characiformes: Crenuchidae) shared by tributaries of upper Tapajós and Xingu river basins, Brazil - Zanata, Angela Maria; Oliveira, Claudio [UNESP]; Oliveira-Silva, Leonardo [UNESP] (Wiley, 2024)
A new species of Characidium shared by adjacent tributaries of the upper portions of the Tapajós and Xingu river basins is described. Characidium varii, new species, can be distinguished from the congeners by having distinctly speckled pattern of colouration, including dark blotches on cheek and ventral surface of head, by having conspicuous dark marks on fins, along with a single row of dentary teeth, isthmus completely covered by scales, 14 circumpeduncular scales, and swimbladder reduced. Molecular data reinforce the validation of the new species. The distribution of C. varii supports the hypothesis of the existence of a faunistic mixing between Tapajós and Xingu river basins, corresponding to the region of the Serra do Cachimbo and surrounding areas, previously proposed in the literature.
Keywords: Brazilian shield; faunistic sharing; freshwater fish; Neotropical; Serra do Cachimbo